2014
DOI: 10.1080/03949370.2014.946539
|View full text |Cite
|
Sign up to set email alerts
|

An experimental approach to test the source of information on kinship in butterfly immatures

Abstract: This study focuses on a non-social species of butterfly of the Neotropical genus Heliconius, H. erato phyllis, where caterpillar-egg cannibalism may occur. In this species, newly hatched caterpillars are able to recognize sibling eggs, preferentially cannibalizing unrelated when there is a choice. The purpose of this study was to verify whether the information to recognize the egg as sibling or non-kin is in the chorion (maternal origin) and/or in the embryo/young caterpillar, by performing both caterpillar-eg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Using an experimental approach, De Nardin and Araújo (2011) showed that first instar caterpillars are prone to recognizing sibling eggs. Further, it was shown that only first instar caterpillars can cannibalize and the source of information for kin recognition is in the egg chorion (DE NARDIN et al, 2015). Moreover, Williams and Gilbert (1981) showed experimentally that structures like stipule tips in Passiflora cyanea (Mast., 1872) and P. oerstedii (Mast., 1872), which resemble eggs, induce females of Heliconius cydno (H.Bates, 1864) to lay fewer eggs than when these structures are absent.…”
Section: Introductionmentioning
confidence: 99%
“…Using an experimental approach, De Nardin and Araújo (2011) showed that first instar caterpillars are prone to recognizing sibling eggs. Further, it was shown that only first instar caterpillars can cannibalize and the source of information for kin recognition is in the egg chorion (DE NARDIN et al, 2015). Moreover, Williams and Gilbert (1981) showed experimentally that structures like stipule tips in Passiflora cyanea (Mast., 1872) and P. oerstedii (Mast., 1872), which resemble eggs, induce females of Heliconius cydno (H.Bates, 1864) to lay fewer eggs than when these structures are absent.…”
Section: Introductionmentioning
confidence: 99%